Go/No-Go Decision-Making Method on Business Development of Software Development in Indonesia - Taufik, Candra; Karyadi, - (Journal of Entrepreneurship, Business and Economics; Vol 6 No 2 (2018), 2018)
Entrepreneurs start their business by planning their business either documented or undocumented. The business plan is executed after considering various aspects of the related business has been met. Execution of business plan (Go / No-Go decision) is thought to be a repeating activity by entrepreneurs as well as innovation that always done for developing and sustaining the business. Effective decision-making method of business plan execution are required to generate time, energy and resource efficiency, especially in the business plan execution of the software development field. This research uses qualitative method with sample size of 9 of software development companies in Indonesia, and it is intended to answer research questions: “What method are effective for entrepreneurs / new entrepreneurs in the field of software development to take Go / No-Go decisions from business plans that have been compiled.” The result of this research is Go / No-Go decision-making method on business development of software development can be decomposed into: Assumption Exploration, assumption selection, assumption testing and take a decision. Some of the main keys are: the business should consider market, product, technology, economy, competition and organization as group of assumptions; and when take a decision, several ways to be taken are: looking at difficulty level and resistance of assumptions, conducting trial and error (doing design fast, and tested to customer), conducting market test and seeing result, and interview with user. Research paper Keywords: Business Development, Decision, Go / No-Go, Method Reference to this paper should be made as follows: Taufik, C., & Karyadi (2018). Go/No-Go Decision-Making Method on Business Development of Software Development in Indonesia, Journal of Entrepreneurship, Business and Economics , 6 (2), 71–90.